Capacity and leadership development for wildlife conservation in sub-Saharan Africa: assessment of a programme linking training and mentorship. Issue 5 (23rd September 2022) - Abu-Bakarr, Ibrahim; Bakarr, Mohamed I.; Gelman, Nancy; Johnny, Jonathan; Kamanda, Philip Jimia; Killian, Dan; Lebbie, Aiah; Murphy, Melanie; Ntongho, Anne; O'Connor, Sheila; Sam-Mbomah, Edwin; Thulla, Philip Foday Yamba; et al.
Abstract: As threats facing wildlife and protected areas across Africa increase, demand for innovative and transformational leadership to tackle the challenges remains high. Traditional academic training programmes are playing a critical role in meeting capacity development needs, yet opportunities for strengthening leadership capabilities are limited. This was the rationale behind Mentoring for ENvironmental Training in Outreach and Resource conservation (MENTOR), initiated in 2007 by the U.S. Fish & Wildlife Service through a collaborative effort with various partners to support conservation leadership and capacity development across sub-Saharan Africa. Five independent programmes were implemented over a decade, each designed to combine rigorous academic and field-based training with mentoring and experiential learning for teams of 8–9 fellows selected through a competitive process. It was envisioned that this approach to leadership and capacity development would strengthen the resolve, capabilities and competences of the fellows and position them as conservation leaders. Using data from interviews and online surveys, we assessed three key aspects of the programmes: strategic relevance and design; progress, effectiveness and impact; and sustainability. Overall, we found that all five programmes successfully delivered the objective of strengthening leadership for conservation in Africa, with the cadre of professionals acquiring new skills and expertise to advance their careers, and developing life-long relationships and networks. We discuss the potential of this approach for developing African conservation leaders.